PERANAN PIMPINAN DALAM MENINGKATKAN KEDISIPLINAN KERJA PEGAWAI BAGIAN PEMERINTAHAN PADA BADAN SATUAN POLISI PAMONG PRAJA KABUPATEN KUTAI BARAT - endy, Efe (PREDIKSI, 2016)
ABSTRACTEFENDI NCAU. Role of Leadership in Improving Employee Work Disciplinary Body Part Reign Civil Service Police Unit West Kutai under the guidance of Mr. DR.Mugni H. Baharuddin MM as a Supervisor I and Mrs. Dra.Hj.NanikPujiastuti, M.Si as Supervisor II.To find the answers to problems that have been formulated and to prove or test the hypotheses of the study and to prove the truth of hypotheses have been put forward.From the analysis of the data found that the Spearman rank correlation coefficient generated is= 0.830 for n = 29. The results are greater when compared with the prices in the table Spearman Rank critical for n = 29, amounting to 0,312.This means that the variable leadershiphad a significant relationship with employee discipline variable On Board Civil Service Police Unit West Kutai.From the comparison valuetables can be seen that there is a significant relationship between the variables of leadership with employee discipline On Board Civil Service Police Unit West Kutai.Wherecount>tables, namely 0.830> 0.312 at a rate sigbifikansi 0.05 for n = 29. Based on the comparison of the data analysis, we can conclude also that the hypothesis proposed in this study can be received and verified.Keywords: Leadership, Discipline Employee Work